2012
DOI: 10.1128/mcb.00167-12
|View full text |Cite
|
Sign up to set email alerts
|

BNip3 Regulates Mitochondrial Function and Lipid Metabolism in the Liver

Abstract: g BNip3 localizes to the outer mitochondrial membrane, where it functions in mitophagy and mitochondrial dynamics. While the BNip3 protein is constitutively expressed in adult liver from fed mice, we have shown that its expression is superinduced by fasting of mice, consistent with a role in responses to nutrient deprivation. Loss of BNip3 resulted in increased lipid synthesis in the liver that was associated with elevated ATP levels, reduced AMP-regulated kinase (AMPK) activity, and increased expression of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
186
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(203 citation statements)
references
References 77 publications
15
186
2
Order By: Relevance
“…Starvation induces BNIP3 expression in the liver, consistent with a role in hepatic function [119]. BNIP3 deficiency is associated with the accumulation of dysfunctional mitochondria in the liver, which is associated with an abnormal metabolic profile.…”
Section: Bnip3 and Nix In Diseasementioning
confidence: 67%
“…Starvation induces BNIP3 expression in the liver, consistent with a role in hepatic function [119]. BNIP3 deficiency is associated with the accumulation of dysfunctional mitochondria in the liver, which is associated with an abnormal metabolic profile.…”
Section: Bnip3 and Nix In Diseasementioning
confidence: 67%
“…BNIP3, a BH3 domain-containing protein that, in some contexts, is considered a proapoptotic protein, likely plays a more important role in mitophagy than in the regulation of apoptosis during nutrient stress. BNIP3 is induced by nutrient deprivation in the liver, where it plays a role in promoting mitophagy and lipid oxidation (Glick et al 2012). BNIP3 expression is induced during the early stages of tumorigenesis but is lost in advanced cancer (Sowter et al 2001(Sowter et al , 2003Okami et al 2004;Abe et al 2005;Akada et al 2005;Erkan et al 2005).…”
Section: Regulation Of Core Autophagy Genes and Cargo Receptors In Camentioning
confidence: 99%
“…In terms of other metabolism-related effects in tissues, a group has reported that BNIP3-null mice livers have higher mitochondrial mass but impaired function compared with control mice [20]. Another study has shown that Bnip3 transcription is upregulated during brown fat adipogenesis [21].…”
Section: Introductionmentioning
confidence: 99%